Signal lamp regulation and control method and system based on urban trunk line vehicle queuing length - ZHANG YINGYING; FENG HAIXIA; ZHANG XINGZI; NING ERWEI; ZHANG MENGMENG; WANG QI; TIAN JUN; LI JIAN; WANG SHUAIQI; LIU KAI (2021)
The invention discloses a signal lamp regulation and control method and system based on urban trunk line vehicle queuing length. The signal lamp regulation and control method comprises the steps of: calculating the maximum queuing length of vehicles in a straight-going lane in a straight-going red light period according to an initial traffic light period, wherein the straight-going red light period refers to the time length from a straight-going red light turn-on moment to a straight-going green light turn-on moment; according to the maximum queuing length of the vehicles on the straight-goinglane in the straight-going red light period, calculating the passing duration required for reaching the number of the vehicles in the straight-going green light period, wherein the straight-going green light time period refers to the time length from the straight-going green light turn-on moment to the straight-going green light turn-off moment; calculating the total duration required for the straight-going vehicles to p